Bhutan - Electronic Government Procurement Readiness Assessment and Roadmap - World Bank (Washington, DC, 2012)
The readiness assessment and roadmap for implementation are the first two components of the Electronic Government Procurement (E-GP) assessment and implementation effort to assist the Royal Government of Bhutan (RGoB) develop an e-GP implementation plan. This work is part of a wider ongoing initiative for public procurement reform, which the RGoB is undertaking with World Bank and other donor funding, which also looks into areas concerning; 1) revisions to the legal framework (i.e. the procurement manual and supporting bidding and consultancy documents), 2) procurement complaints mechanisms, 3) the establishment of a public procurement policy mechanism, and 4) procurement capacity building through existing national training institutions. Under the agreed work plan for wider procurement reforms, the RGoB, in collaboration with the Bank and other donors in Bhutan, is working on the following areas: a) renewing the procurement manual and its accompanying standard bidding documents and request for proposals (largely completed), b) creating a public procurement policy mechanism, c) addressing the need for procurement grievance mechanisms, d) building the capacity of national institutions responsible for training people on public procurement, and e) introducing electronic forms of procurement. A key feature of an effective public procurement system is accountability, and accountability is driven by two ingredients - the probability of discovery and the consequences of the discovery of malpractice and negligence.